Crosstalk Between Circulating Follicular T Helper Cells and Regulatory B Cells in Children With Extrinsic Atopic Dermatitis - Jiang, Jinqiu; Yan, Shi; Zhou, Xiaoying; Zhou, Jinghua; Bai, Xiaoming; Tan, Qi; Xia, Yunqiu; Wang, Hua; Luo, Xiaoyan (Frontiers in Immunology, 2021)
Atopic dermatitis (AD) in early childhood is often the initial manifestation of allergic disease associated with high IgE. Accumulating evidences show that follicular helper T (Tfh) cells play a critical role in promoting B cell differentiation and IgE production, human regulatory B (Breg) cells participate in immunomodulatory processes and inhibition of allergic inflammation. However, the roles and interactions between IL-10-producing Breg cells and Tfh cells in childhood AD are unclear. In this study, we found that the percentage of CD19+IL-10+ Breg cells in children with extrinsic AD was significantly lower than that in age-matched healthy controls, and that it correlated negatively with enhanced CD4+CXCR5+PD-1+ICOS+ circulating Tfh cell responses and increased disease activity; however, there was no significant correlation with serum total IgE levels. A co-culture system revealed that Breg cells from patients with extrinsic AD cannot effectively inhibit differentiation of Tfh cells in an IL-10 dependent manner. Abnormal pSTAT3 signaling induced via Toll-like receptors (TLR), but not the B-cell receptor (BCR) signaling, might contribute to the defect of Breg cells in AD. Taken together, these observations demonstrate an important role for IL-10-producing Breg cells in inhibiting Tfh cell differentiation, and suggest that they may participate in the pathogenesis of AD.